Causes of high blood O2 affinity of animals living at high altitude - Petschow, D; Würdinger, I; Baumann, R; Duhm, J; Braunitzer, G; Bauer, C (Journal of applied physiology: respiratory, environmental and exercise physiology, 1977)
We have measured the partial pressure of O2 at 50% saturation (P50) and the concentration of various phosphate compounds in the erythrocytes of the bar-headed goose and the guanaco to establish the cause of the high blood O2 affinity in animals who normally reside at high altitude. The same data were obtained in the blood of two goose species, that live at sea level, and in human blood. At standard conditions (pH 7.4, PCO2 40 Torr, 37 degrees C), P50 was 29.7 Torr in the blood of the bar-headed goose and was about 10 Torr higher in the goose species living at sea level. Since the concentration of organic phosphates was not markedly different in the erythrocytes of either goose species we conclude that the hemoglobin of the bar-headed goose reacts more weakly with organic phosphates, which can also be inferred from studies on purified hemoglobin solutions. Likewise, the low P50 of guanaco blood in comparison with human blood can be explained by a reduced interaction of 2,3-bisphosphoglycerate of guanaco hemoglobin compared to the human pigment.